Gender At The Helm: Examining The Relationship between The CEO ‎Gender and ESG Performance in S&P 500 Companies - Merter, Abdullah Kürşat; Balcıoğlu, Yavuz Selim; Karakaya, Turhan (International Journal of Accounting and Economics Studies, 2025)
Gender diversity in corporate leadership and ESG performance represents a critical research area in ‎accounting and economics. While organizations face mounting pressure to demonstrate sustainable ‎business practices, the persistent underrepresentation of women in executive positions presents a unique ‎opportunity to examine how leadership characteristics influence corporate sustainability outcomes. The ‎present study examines the relationship between chief executive officers (CEOs') gender and ESG ‎component performance among S&P 500 companies, specifically investigating whether female leadership ‎influences the environmental, social, and governance dimensions differently and testing hypotheses ‎derived from upper echelon theory, stakeholder theory, and agency theory. The analysis employs a ‎comprehensive dataset of 426 S&P 500 companies over 2022-2023, including 36 female-led and 390 ‎male-led companies. Multiple regression models are utilized to analyze the relationship between CEO ‎gender and ESG component scores while controlling for factors such as company size, profitability, ‎leverage, year effects, and industry fixed effects. Robustness checks encompass propensity score ‎matching and year-specific analyses. Female chief executive officers demonstrate a marked tendency to ‎outperform their male counterparts in terms of social ESG dimensions while concurrently demonstrating ‎underperformance in the environmental and governance dimensions. The net effect of these offsetting ‎factors is that there is no significant difference in overall ESG scores. The findings remain consistent across ‎robustness checks and suggest that female leadership prioritizes stakeholder-oriented social initiatives while ‎allocating relatively fewer resources to environmental and governance improvements. The study revealed ‎that the impact of CEO gender on ESG performance is not uniform across all components, but rather, it is ‎component-specific. This finding supports theoretical predictions about gender-differentiated leadership ‎styles and strategic priorities. The findings have important implications for corporate governance practices, ‎investor decision-making, and policy development in the evolving landscape of corporate sustainability‎.
Keywords: CEO Gender; Corporate Governance; Environmental Social Governance; Female Leadership; ‎Sustainability Performance